THE TRUE NORTH, STRONG AND FREE - Mikhail B. Bashkirov; Marina Yu. Velizhanina (Сравнительная политика)
Book review: Maximova, D.D.; Sokolov, V.I. Sever i Arktika v politike i khoziaistve Kanady (North and Arctic in Politics and Economy of Canada). Moscow: Institute for the U.S. and Canadian Studies, 2015. 140 p.